Scheduling Algorithm: Tasks Scheduling Algorithm for Multiple Processors with Dynamic Reassignment. (24th April 2008) - Yadav, Pradeep Kumar; Singh, M. P.; Kumar, Harendra
Abstract : Distributed computing systems [DCSs] offer the potential for improved performance and resource sharing. To make the best use of the computational power available, it is essential to assign the tasks dynamically to that processor whose characteristics are most appropriate for the execution of the tasks in distributed processing system. We have developed a mathematical model for allocating "M " tasks of distributed program to "N " multiple processors (M > N ) that minimizes the total cost of the program. Relocating the tasks from one processor to another at certain points during the course of execution of the program that contributes to the total cost of the running program has been taken into account. Phasewise execution cost [EC], intertask communication cost [ITCT], residence cost [RC] of each task on different processors, and relocation cost [REC] for each task have been considered while preparing a dynamic tasks allocation model. The present model is suitable for arbitrary number of phases and processors with random program structure.